2021
DOI: 10.1108/ijqrm-12-2020-0412
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the factors affecting customer lifetime value

Abstract: PurposeThe main objective of this paper is to investigate the factors affecting customer lifetime value (CLV) for Internet service providers in Jordan, namely, technical quality, functional quality, brand credibility, confidence benefits, special treatment benefits, customer satisfaction and commitment.Design/methodology/approachAn online survey was conducted involving a sample of 481 respondents. SPSS was used to analyse the data and test the proposed relationships, while SmartPLS was used to examine the robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 89 publications
(196 reference statements)
3
14
0
Order By: Relevance
“…An insignificant relationship, however, was found between environment quality (significance value = 0.796) and WOM. Similarly, this finding is consistent with Dandis et al (2021) who reported that functional and technical quality could not contribute to customer satisfaction. However, this finding is not consistent with Abdullahi and Yusoff (2019) who reported that physical building features and non-physical building features comprise a valuable predictor of the inclination of positive WOM from students.…”
Section: Discussionsupporting
confidence: 91%
“…An insignificant relationship, however, was found between environment quality (significance value = 0.796) and WOM. Similarly, this finding is consistent with Dandis et al (2021) who reported that functional and technical quality could not contribute to customer satisfaction. However, this finding is not consistent with Abdullahi and Yusoff (2019) who reported that physical building features and non-physical building features comprise a valuable predictor of the inclination of positive WOM from students.…”
Section: Discussionsupporting
confidence: 91%
“…These results support other empirical studies (Dandis et al 2022c;Fatikhaturrohmah et al, 2020;Fatima and Mascio, 2020;Wong et al, 2019;Chou and Chen, 2018;Yang et al, 2017;Dagger and Brien, 2010;Kim and Ok, 2009) that find significant connections between relationship marketing outcomes and the above variables.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Chou and Chen (2018) agreed that these gains had a positive impact on commitment. Dandis et al (2022c) also observed that special treatment benefits had a significant positive impact on customer commitment and satisfaction. Moreover, Fatikhaturrohmah et al (2020) indicated that these benefits had a significant influence on the trust and satisfaction of customers.…”
Section: Special Treatment Benefits Customer Satisfaction Commitment ...mentioning
confidence: 84%
See 1 more Smart Citation
“…This implies that studies on relationship benefits and brand experiences in the FFRs have been largely ignored, particularly in emerging markets. Therefore, this research contributes to these discussions by addressing the calls of researchers to examine relational benefits (Dandis et al, 2022a) brand experiences (Safeer et al, 2021;Ong et al, 2018) in a non-Western context. Moreover, not much is known about how each type of brand experience influence outcomes of CRM (Ong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%